Energy Conversion in Natural and Artificial Photosynthesis - Brinkert, Katharina (Springer Series in Chemical Physics,, 2018)
This book discusses the basic principles and processes of solar energy conversion in natural photosynthesis. It then directly compares them with recent developments and concepts currently being pursued in artificial photosynthetic systems that are capable of utilizing sunlight to convert carbon dioxide and water into a chemical fuel. In this regard, the main focus is on photoelectrochemical cells, in which semiconducting photoanodes and -cathodes modified with (electro-) catalysts are used to oxidize water, produce hydrogen and reduce carbon dioxide in a monolithic device. The fundamental photochemical and photophysical processes involved are presented and discussed, along with protection mechanisms and efficiency calculations for both natural and artificial photosynthesis. In turn, key parameters that are crucial for the efficient operation of natural photosynthesis are identified. Lastly, their validity and applicability in the design of artificial solar-driven water-splitting systems are examined. .